Answer:
A.)
![K_b = ([CH_3NH_3^+][OH^-])/([CH_3NH_2])](https://img.qammunity.org/2023/formulas/chemistry/college/6yugp4m444lb9ih9g8vtzvpp2vy716qxcx.png)
Step-by-step explanation:
The general Kb expression is:
![K_b = ([HA][OH^-])/([A^-])](https://img.qammunity.org/2023/formulas/chemistry/college/o24rkvchtpqmrt7agu2axqn94v81h1illu.png)
In this equation
-----> Kb = equilibrium constant
-----> [HA] = acid
-----> [A⁻] = base
Since liquids are not included in equilibrium expressions, H₂O should not be present. The products are in the numerator while the reactant are in the denominator. In this reaction, CH₃NH₂ is acting as a base and CH₃NH₃⁺ is acting as an acid.
As such, the expression is:
![K_b = ([CH_3NH_3^+][OH^-])/([CH_3NH_2])](https://img.qammunity.org/2023/formulas/chemistry/college/6yugp4m444lb9ih9g8vtzvpp2vy716qxcx.png)